Trails of Saami Self-Consciousness - Paine, Robert (Anthropologica, 2022)
A cluster of issues are addressed: How Saami have handled a stigmatized identity vis-a-vis the Norwegians; how a rewarding sense of "being Saami'' has been expressed within local communities; how striving for a "national" expression provokes ethnopolitical struggles among themselves and not just vis-a-vis the Norwegians. And ?how do Saami intellectuals handle non-Saami writings about these issues?